Air pollution and the number of daily deaths due to respiratory causes in Tehran. (1st February 2021) - Karimi, Behrooz; Shokrinezhad, Behnosh
Abstract: Air pollution is a major environmental and health issue around the world in the past decades. The main objective of this project was to evaluate the association between the number of daily respiratory deaths and air pollution concentrations among residents of Tehran. Air pollution parameters such as particulate matter (PM), carbon monoxide (CO), sulfur dioxide (SO2 ), ozone (O3 ), and nitrogen dioxide (NO2 ) were obtained from the Tehran air quality control company. We recognized the number of daily respiratory mortality data from Tehran's cemetery registration from 2014 to 2019. We employed a Poisson regression model with natural spline functions to adjust air pollution and daily respiratory mortality data with temperature, long-term, and seasonality. The mean concentrations of PM2.5, PM10, O3, CO, SO2, and NO2 were 29.8 μg/m 3, 78.7 μg/m 3, 220.4 part per billion (ppb), 2.3 part per million (ppm), 9.7 ppb, and 49.6 ppb, respectively. The percent change and 95% confidence intervals (CIs) for mortality from respiratory causes due to 10-μg/m 3 increment in PM2.5 and PM10 concentrations were 4.5% (95% CI: 0.3–9.5%) and 2.5% (95% CI: 0.1–3.5%) in the adjusted model, respectively. The percent change of respiratory death was significant for SO2 (2.8% per 1 ppb increment, 95% CI: 0.5–19.5%), NO2 (1.5% per 1 ppb increment, 95% CI: 0.8–15%) and O3 (0.6% per 1 ppb increment, 95% CI: 0.1–1.1%) exposure in adjusted model. Stronger associations obtained among elderly and women subjects. Conclusively, the findings of the present study suggest that the risk of respiratory death was associated with PM2.5, PM10, SO2, NO2, and O3 exposure. Highlights: Percent change of respiratory mortality due to PM2.5 and PM10 exposure was 4.5% and 2.5% respectively. Percent change of respiratory mortality due to CO and SO2, exposure was 2.1% per 1 ppm and 2.8% per 1 ppb, respectively. The elderly and women were more sensitive to PM2.5, PM10, and SO2 than the younger and men age.